A microearthquake survey of Bouvet Island, South Atlantic - Kristoffersen, Yngve; Bungum, Hilmar (Tectonophysics, 1982)
A microearthquake survey carried out during the 1978–1979 Norwegian Antarctic Research Expedition indicates that only minor seismic activity is associated with the Bouvet volcano.
Keywords: Bouvetøya; NARE 1978/79; geofysikk; seismologi; vulkaner

Aeromagnetic reconnaissance over the Riiser-Larsen Ice Shelf, east Antarctica - Kristoffersen, Yngve; Aalerud, Jan (Polar Research, 1988)
Keywords: Antarktis; glasiologi; havbunnen; isbreer; isfront; seismologi

Seismic investigations in the Weddell Sea Embayment - Haugland, Kristen; Kristoffersen, Yngve; Velde, Anders (Tectonophysics, 1985)
Keywords: Antarktis; NARE 1976/77; NARE 1978/79; Weddellhavet; ekspedisjoner; seismologi

The seismicity of the Bouvetøya region - Bungum, Hilmar; Kristoffersen, Yngve; Nilsen, Alf K. (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; seismologi; vulkaner